The Impact of the COVID-19 Pandemic on Police Involvement in Mental Health Calls for Service - Tartaro, Christine (Criminal justice policy review, 2025)
The onset of the COVID-19 pandemic not only threatened individuals’ physical health but also caused a serious strain on mental health and access to care. Analyzing 4 years of data from 2019 through 2022, this study examines whether the frequency of mental health calls for service and police-initiated stops for mental health reasons changed over the course of the COVID-19 pandemic. Using interrupted time-series analysis, the results show that police involvement in mental health care was significantly affected by the COVID-19 pandemic. However, different changes were observed between dispatched calls for service and police-initiated stops for mental health reasons.